1985
DOI: 10.1093/jn/115.8.1065
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Uptake of Insulin and Glucagon by Liver in Rats Adapted to a High Protein Diet

Abstract: The regulatory role of the liver with regard to circulating concentrations of insulin and glucagon was investigated in rats adapted to high carbohydrate (HC) or high protein (HP) diets, during the period of maximal nutrient absorption. In rats fed HC diet, high secretion of insulin into portal vein in conjunction with low hepatic uptake elicited systemic hyperinsulinemia. In rats fed HP diet, both insulin and glucagon were secreted in large amounts, but hormone removal by the liver was greater than in rats fed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Previous studies had reported a postprandial secretion of both insulin and glucagon in rats fed a HP diet (3,18). In that context, the respective influence of amino acids and insulin on glucagoninduced PEPCK and G6PC1 gene expression was investigated in vitro in primary cultures of isolated hepatocytes with constant concentration of glucose (5.5 mM).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had reported a postprandial secretion of both insulin and glucagon in rats fed a HP diet (3,18). In that context, the respective influence of amino acids and insulin on glucagoninduced PEPCK and G6PC1 gene expression was investigated in vitro in primary cultures of isolated hepatocytes with constant concentration of glucose (5.5 mM).…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, we studied the time course changes of energy metabolism during the transition from a normal to an HP diet in rats. Thus, we were able to follow the metabolic adjustments occurring during the 15-d period in which adaptation of protein and energy metabolism to the diet was achieved (36)(37)(38). 21 ) was added at the expense of sucrose and starch.…”
Section: Introductionmentioning
confidence: 99%
“…Our results clearly demonstrate that the fraction of intraportally infused insulin reaching the systemic circulation decreases with higher doses of insulin. This implies that the liver contains adaptable mechanisms to reduce the systemic insulin levels 119, 37,49]. These mechanisms are not only regulated by the portal insulin levels, but are also under the control of other factors [37,50].…”
Section: Discussionmentioning
confidence: 99%